The key agent of history - Mishalova, Olena (Actual Problems of Mind, 2020)
The paper is devoted to the consideration of the views on the problem of the key agent of history. There are two positions: the concepts of an apersonalized creator of history and the concepts of a personalized agent of history. For the first group it is typical to see the maim creator of history in some supernatural beings, which a person cannot perceive directly with the help of the senses or the mind, but he/she is able to observe their influence on the course of history. For example, it may be God in the Abrahmic religious (Judaism, Christianity, Islam), the fate and gods of the ancient Greeks and Romans, Hegel’s Absolute Spirit. The second position includes ideas about the personalized agent of history: an outstanding historical figure (politician, prince, religious prophet, hero, charismatic leader, passionary, Nietzche’s superman, poet or artist), a social group (social class, social stratum, ruling elite, aristocracy, creative minority, technical intellectuals, «new» intellectuals of post-industrial society, technocrats, social movements), large collective communities (people, nation, race, ethnos, culture and/or civilization, cultural-historical types, crowds and masses, humanity in general). The author shows that all the considered position are united by the common opinion that the human past is the result of the systemic activity of many historical agents, but the dominant progressive role is usually assigned to only one of them. The paper also introduces a new concept «agent of history» to refer to an outstanding historical figure (social group or large collective community) who, through its actions or inactions, creates history.